(untitled) (Élisée - Revista de Geografia da UEG, 2025)
Geomorphology in Brazil had its first steps and major ruptures under the influence of foreign geographers, mainly French. These researchers contributed a lot to the methodological organization of research in Geomorphology in Brazil. Among these geographers stands out Jean Tricart. To understand the directions taken by geomorphological research in Brazil, it is necessary to seek its epistemological roots and understand some debates, including philosophical ones about Nature. In this context, this brief contribution aims to elucidate how Jean Tricart, a French geographer with an important role in the constitution of Brazilian Geomorphology, became the bridge between discussions of nature undertaken from organic conceptions of nature and Brazilian Geomorphology. Jean Tricart was influenced by a discussion of Organic Nature, initiated in Ancient Greece, rescued by Kant and his successors, later discussed in the General Theory of Systems, current followed and defended by Tricart. He, in turn, influenced the works of Brazilian geographers who addressed the territorial dynamics and the anthropization of the landscape, either directly or indirectly.